Vertex operator superalgebras associated with affine Lie superalgebras. Issue 6 (3rd June 2017) - Zheng, Lisun
ABSTRACT: It is proved that the induced moduleV 𝔤 ̂ ( k, 0 ) of level k associated with a finite dimensional simple Lie superalgebra 𝔤 with a nondegenerate even supersymmetric invariant bilinear form is a ℤ -graded vertex operator superalgebra, and the explicit expression for the virasoro algebra on any twistedV 𝔤 ̂ ( k, 0 ) -module is given.